Edukasi Pemanfaatan Aplikasi Teknologi Finansial (Fintech) kepada Masyarakat Desa Kapita, Kabupaten Jeneponto, Sulawesi Selatan - Muhammad Ashoer; Hukma Ratu Purnama; Munawir Nasir; A. Faisal Bahari; Andika Pramukti (Yumary: Jurnal Pengabdian kepada Masyarakat, 2022)
Purpose: Financial technology (financial technology – fintech) is a breakthrough that connects directly between the financial sector and the general public. However, the understanding of fintech concepts and practices in rural areas is still under-explored. To solve this, this educational and service community activity aims to uncover the views and mindsets of rural communities on the urgency of using fintech applications in everyday life. Method: The selected target participants were the people of Kapita village, Jeneponto Regency, South Sulawesi, totaling 55 people. The method of implementation is carried out by describing the content and practices of Fintech with the lecture teaching. Next, simulate the use of one of the fintech applications directly via a smartphone. Finally, the evaluation is carried out with a questionnaire to measure the level of understanding and interest in people's behavior towards Fintech. Result: The results showed that the participants fintech understanding had not yet reached the specified target, but their interest and desire for the use of fintech in the future was very high. This could be a golden opportunity for the stakeholder to develop and maximize the early intention of the rural financial behavior. Conclusion: Based on the results, it can be concluded that this program was conducted succesfully and already fulfilled the planned goal. In the future, we also hope that this Fintech educational project could be an essential resource to stimulate the intention and attitude of the Kapita village community towards the development of financial technology use in Indonesia.